Implementation of TQM and the Integration of BIM in the Construction Management Sector in Saudi Arabia - Mohammad Abazid; Hüseyin Gökçekuş; Tahir Çelik (Advances in Materials Science and Engineering)
Total Quality Management (TQM) is based on the conceptions of managing and enhancing the success of construction projects. When applied, TQM improves execution of time management of project, satisfies clients’ needs, minimizes the expenses and increases the profit of contractor, and fulfils safety regulations on the construction site. This research is aimed at evaluating the impacts of employing the concepts of TQM to the construction projects in Saudi Arabia. The results of the study were obtained through utilization of a descriptive analytical approach, where 300 questionnaires were distributed to engineering firms and companies with a response rate of 200 questionnaires, hence achieving the study sample for this research. The data gathered was analyzed by applying the Statistical Package for Social Science (SPSS) program and calculating the relative importance index (RII) and the mean values. From the research conducted, the outcomes showed that the management’s ability to commit using TQM while applying BIM obtained a relative importance of (0.717), while the relative importance for the management’s ability to commit using TQM without the application of BIM is (0.552). The results showed that construction projects in Saudi Arabia still sustain setbacks from applying TQM concepts and suffer from the lack of administrative, scientific, and technical applications.